Momordica charantia ointment accelerates diabetic wound healing and enhances transforming growth factor-β expression - Norhazilah, Muhamad; Farida, Hussan; Seong Lin, Teoh (2014)
Objective: Transforming growth factor-β (TGF-β) plays an important role in wound healing. Delayed wound healing is a consequence of diabetes, leading to high morbidity and poor quality of life. Momordica charantia (MC) fruit possesses anti-diabetic and wound healing properties. This study aimed to explore the changes in TGF-β expression in diabetic wounds treated with topical MC fruit extract. Methods: Fifty-six male Sprague-Dawley rats were divided into a normal control group and five diabetic groups of ten rats each. Intravenous streptozotocin (50mg/kg) was given to induce diabetes in the diabetic groups. Full thickness excision wounds were created on the thoracodorsal region of the animals, and these wounds were then treated with vehicle, MC powder, MC ointment and povidone ointment or ointment base for ten days. Wound healing was determined by the rate of wound closure, total protein content and TGF-β expression in the wounds, and histological observation. Results: Diabetic groups showed delayed wound closure rates compared to the control group. The wound closure rate in the MC ointment group was significantly faster than that of the untreated diabetic group (p<0.05). The MC ointment group also showed intense TGF-β expression and a high level of total protein content. Conclusion: MC ointment has a promising potential for use as an alternative topical medication for diabetic wounds. This work has shown that it accelerates wound healing in diabetic rats, and it is suggested here that this occurs by enhancing TGF-β expression. Further work is recommended to explore this effect. Declaration of interest: There is no conflict of interest.